Impact of Managed Early Postoperative Complications on Clinical Outcomes in Patients Undergoing Transurethral Resection of the Prostate (The Planet, 2025)
Background: Transurethral resection of the prostate (TURP) is the gold standard operation for symptomatic benign prostatic hyperplasia (BPH), but early postoperative complications can affect outcomes. The objective was to examine the prevalence and association of comorbidities with early postoperative complications and outcomes following TURP. Methods & Materials: The prospective observational study was conducted in BIRDEM General Hospital, Dhaka, between November 2016 and May 2017, on 50 BPH patients who were subjected to TURP. Demographics, comorbidities, perioperative parameters, complications, management strategies, and outcomes were gathered. Statistical analysis was performed using SPSS version 20. Results: Mean patient age was 68.7±8.1 years, with 52% of patients aged 61-70 years. Comorbidities were present in 84% of patients, most frequently diabetes mellitus (66%), urinary tract infections (54%), and chronic kidney disease (34%). Prostate size was a mean of 54.3±30.7g with 18.6±9.3g of tissue resected. Early postoperative complications occurred in 22% of patients, most frequently hematuria (16%). Treatment modalities comprised irrigation of bladder (8%), tranexamic acid (2%), or combination therapy (6%) for hematuria, while clot retention (8%) was managed equally by Tommy syringe evacuation or cystoscopy. Despite the complications, complete resolution without sequelae was observed in 90.91% of the affected patients. Conclusion: Despite the large comorbidity in patients undergoing TURP, appropriate management of early postoperative complications results in a favorable outcome in most patients. Careful preoperative assessment, optimization of comorbidity, and management of complications early are required to enhance the safety and efficacy of TURP in an increasingly complex patient population.
Keywords: TURP; BPH; Prostate